The Performance Evaluation of Voip for a Mobile User - Fadhil, Diyar Salah; Rasul, Ababakr Ibrahim; Muhammed, Younus Ameen (Discoveries in Agriculture and Food Sciences, 2017)
Broadband Wireless Access (BWA) technology has developed rapidly and it has dominated the advancement of technology especially in wireless networks. This paper studies the performance evaluation of VoIP for a mobile user and how the QoS parameters vary for different speeds. The purpose of the study is to examine the effect of mobility of a user on the performance of VoIP. In the meanwhile, it is evaluating the simulation and emulation method for its validity to be used for any new upcoming technology. However, the results of the simulation need to be verified and assessed by emulation tested results, hoping that both results match closely with each other.